2022
DOI: 10.1039/d2py00774f
|View full text |Cite
|
Sign up to set email alerts
|

Tracking side reactions of the inverse vulcanization process and developing monomer selection guidelines

Abstract: Various olefin monomers were inverse-vulcanized. The structural analysis and evaluation of the thermal stability of the products revealed that aliphatic internal olefins are suitable monomers for suppressing side reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…As expected, the 1 H NMR spectrum shows three multiplet signals, centered at δ 5.79, 4.88 and 4.84 ppm, and the 13 C NMR spectrum presents signals at δ 135.0, 113.2 and 24.9 ppm, all of them corresponding to the allyl groups. In the 29 Si NMR spectrum, a single signal appears at δ −3.5 ppm, which is consistent with the value observed for the analogous ferrocene derivative with two vinylsilane groups. 61 To investigate the reactivity of the two allyl groups (covalently linked to the organometallic unit in co-monomer 1) against elemental sulfur, different vulcanization reaction conditions were tested.…”
Section: Papersupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, the 1 H NMR spectrum shows three multiplet signals, centered at δ 5.79, 4.88 and 4.84 ppm, and the 13 C NMR spectrum presents signals at δ 135.0, 113.2 and 24.9 ppm, all of them corresponding to the allyl groups. In the 29 Si NMR spectrum, a single signal appears at δ −3.5 ppm, which is consistent with the value observed for the analogous ferrocene derivative with two vinylsilane groups. 61 To investigate the reactivity of the two allyl groups (covalently linked to the organometallic unit in co-monomer 1) against elemental sulfur, different vulcanization reaction conditions were tested.…”
Section: Papersupporting
confidence: 87%
“…Compound 1 was isolated as an air-stable, orange oil, which was purified by column chromatography. The structure of precursor 1 was confirmed by 1 H, 13 C and 29 Si Nuclear Magnetic Resonance (NMR) and Attenuated Total Reflectance InfraRed (ATR-IR) spectroscopies and mass spectrometry (see ESI †). As expected, the 1 H NMR spectrum shows three multiplet signals, centered at δ 5.79, 4.88 and 4.84 ppm, and the 13 C NMR spectrum presents signals at δ 135.0, 113.2 and 24.9 ppm, all of them corresponding to the allyl groups.…”
Section: Papermentioning
confidence: 98%
“…At higher temperatures, it is the conversion of isopropenyl/alkyl propenyl moieties into dithiole thione groups with evolution of H 2 S that has been reported to occur . More recently, this has elegantly been experimentally confirmed by Kanbara and co-workers for reactions of S 8 with MeSty, as noted by the formation of the dithiole thione and H 2 S . This oxidative process could in principle be a source of H-atoms required for thiocumyl fragment formation, but would presume near stoichiometric generation of H 2 S gas during the inverse vulcanization of S 8 and DIB.…”
Section: Resultsmentioning
confidence: 85%
“…At higher temperatures, it is the conversion of isopropenyl/ alkyl propenyl moieties into dithiole thione groups with evolution of H 2 S that has been reported to occur. 65 More recently, this has elegantly been experimentally confirmed by Kanbara and co-workers for reactions of S 8 with MeSty, as noted by the formation of the dithiole thione and H 2 S. 66 This oxidative process could in principle be a source of H-atoms required for thiocumyl fragment formation, but would presume near stoichiometric generation of H 2 S gas during the inverse vulcanization of S 8 and DIB. While some generation of H 2 S has been reported during inverse vulcanization with DIB, 53 visible bubbling of the reaction media is not observed under most bulk polymerization conditions, in contrast with inverse vulcanizations of S 8 with 1,3-phenylene diamine, 18 or reactions that have undergone thermal runaway.…”
Section: Simulations Of Chemo-and Regioselectivity Of Thiyl Radicals ...mentioning
confidence: 81%
“…This case study suggested that 1,2-dithiole-dithiones in relation to this Raman analysis should be investigated through a combination of experimental and computational methods. 36…”
Section: Polymer Chemistry Papermentioning
confidence: 99%